Teaching Method: The Use of Engage, Study, and Activate (ESA) on Students’ Vocabulary Mastery - Ishak (Abdul Media Literasi, 2024)
The purpose of the research is to investigate whether the Engage, Study, and Activate (ESA) method was effectively used by eighth grade students for vocabulary mastery. The researcher used quantitative approach by the design of this study was quasi-experimental research to determine the effectiveness of the Engage, Study, and Activate (ESA) method on vocabulary mastery. The population of the research consisted of 205 students, and the sample of the research was the eighth grade of SMP Negeri 5 Tangerang for the academic year 2021-2022, which consisted of 60 students. The results of the research showed that the students’ vocabulary in the pre-test and post-test differed significantly, up to 20 percent. After receiving the treatment, their vocabulary significantly improved. This can be seen from the average pre-test results in the experimental class of 61.6 and the average post-test of 74.13. The mean of the pre-test results in the control class was 58.66, and the average post-test results were 64.26. The value of the t-test was greater than the t-table (5.40 > 2.00). It indicated that the alternative hypothesis (H1) was accepted and the null hypothesis (H0) was rejected. It can be concluded that the use of the Engage, Study, and Activate (ESA) method is effective in improving vocabulary mastery.